REVITALISASI PENDIDIKAN KELUARGA SEBAGAI BASIS PERLINDUNGAN ANAK - Sumiarti Sumiarti (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
The family was the first and foremost education for children. Family supposed to be a safe place, comfortable and conducive to growth and development children. Fact, sometimes in the family actually happens a violation of the rights of children of the act of violence and evil, good being done by parents and other family members. Hence, to revitalize to education in family is very important to restore the role of education family as the base protection against children.